EAU-EANM-ESTRO-ESUR-ISUP-SIOG Guidelines on Prostate Cancer—2024 Update. Part I: Screening, Diagnosis, and Local Treatment with Curative Intent - Cornford, Philip; van den Bergh, Roderick C.N.; Briers, Erik; Van den Broeck, Thomas; Brunckhorst, Oliver; Darraugh, Julie; Eberli, Daniel; De Meerleer, Gert; De Santis, Maria; Farolfi, Andrea; Gandaglia, Giorgio; Gillessen, Silke; et al. (European urology, 2024)
The evidence in the field of diagnosis, staging, and treatment of localised prostate cancer (PCa) is evolving rapidly. The 2024 European Association of Urology (EAU)-European Association of Nuclear Medicine (EANM)-European Society for Radiotherapy and Oncology (ESTRO)-European Society of Urogenital Radiology (ESUR)-International Society of Urological Pathology (ISUP)-International Society of Geriatric Oncology (SIOG) guidelines on PCa summarise the most recent findings and advice for their use in clinical practice. These PCa guidelines reflect the multidisciplinary nature of PCa management. The European Association of Urology (EAU)-European Association of Nuclear Medicine (EANM)-European Society for Radiotherapy and Oncology (ESTRO)-European Society of Urogenital Radiology (ESUR)-International Society of Urological Pathology (ISUP)-International Society of Geriatric Oncology (SIOG) guidelines provide recommendations for the management of clinically localised prostate cancer (PCa). This paper aims to present a summary of the 2024 version of the EAU-EANM-ESTRO-ESUR-ISUP-SIOG guidelines on the screening, diagnosis, and treatment of clinically localised PCa. The panel performed a literature review of all new data published in English, covering the time frame between May 2020 and 2023. The guidelines were updated, and a strength rating for each recommendation was added based on a systematic review of the evidence. A risk-adapted strategy for identifying men who may develop PCa is advised, generally commencing at 50 yr of age and based on individualised life expectancy. The use of multiparametric magnetic resonance imaging in order to avoid unnecessary biopsies is recommended. When a biopsy is considered, a combination of targeted and regional biopsies should be performed. Prostate-specific membrane antigen positron emission tomography imaging is the most sensitive technique for identifying metastatic spread. Active surveillance is the appropriate management for men with low-risk PCa, as well as for selected favourable intermediate-risk patients with International Society of Urological Pathology grade group 2 lesions. Local therapies are addressed, as well as the management of persistent prostate-specific antigen after surgery. A recommendation to consider hypofractionation in intermediate-risk patients is provided. Patients with cN1 PCa should be offered a local treatment combined with long-term intensified hormonal treatment. The evidence in the field of diagnosis, staging, and treatment of localised PCa is evolving rapidly. These PCa guidelines reflect the multidisciplinary nature of PCa management. This article is the summary of the guidelines for “curable” prostate cancer. Prostate cancer is “found” through a multistep risk-based screening process. The objective is to find as many men as possible with a curable cancer. Prostate cancer is curable if it resides in the prostate; it is then classified into low-, intermediary-, and high-risk localised and locally advanced prostate cancer. These risk classes are the basis of the treatments. Low-risk prostate cancer is treated with “active surveillance”, a treatment with excellent prognosis. For low-intermediary-risk active surveillance should also be discussed as an option. In other cases, active treatments, surgery, or radiation treatment should be discussed along with the potential side effects to allow shared decision-making.